Cation Exchange Capacity of Barrow Soils - T.K. Raab; D.A. Lipson (Arctic Data Center, 2013)
Cation exchange capacity (CEC) and porosity-weighted CEC (Qv) for soils of drained thaw lake basins near Barrow, AK representing young, medium, old and ancient age classes. See Lipson et al. (2013) GBC 27:111.